Access to Enantioenriched Spiro‐ϵ‐Lactam Oxindoles by an N‐Heterocyclic Carbene‐Catalyzed [4+3] Annulation of Flexible Oxotryptamines with Enals. Issue 48 (1st August 2019) - Liu, Dehai; Hu, Zhouli; Zhang, Yuxia; Gong, Minghua; Fu, Zhenqian; Huang, Wei
Abstract: Oxotryptamines were firstly used as flexible four‐atom synthons in an NHC‐catalyzed formal [4+3] annulation, providing a novel enantioselective method to access structurally diverse spiro‐ ϵ ‐lactam oxindoles with excellent enantioselectivities. This metal‐free reaction features a broad substrate scope, excellent functional‐group tolerance and proceeds under mild reaction conditions. Importantly, enantiopure privileged hexahydropyrroloindoles could be easily constructed by a one‐pot process from the resulting spiro‐ ϵ ‐lactam oxindoles. Abstract : Organocatalysis : Oxotryptamine was used as a flexible four‐atom synthon in an NHC‐catalyzed formal [4+3] annulation, providing an enantioselective method to access structurally diverse spiro‐ ϵ ‐lactam oxindoles with excellent enantioselectivities. This metal‐free reaction features a broad substrate scope, excellent functional‐group tolerance and proceeds under mild reaction conditions (see scheme).